Shelf life extension of rainbow trout fillets by application of edible chitosan films impregnated with postbiotic of Pedicoccocus acidilactici - Akgol, Muzeyyen; Karatepe, Pinar; Incili, Gokhan Kursad; Tekin, Ali; Oksuztepe, Gulsum; Hayaloglu, Ali Adnan (Elsevier, 2025)
The aim of the study was to characterize the postbiotic and edible films formed by the mixture of postbiotic and chitosan, and to evaluate the effects of the films on the shelf life of rainbow trout fillets at different storage temperatures (4 and 10 degrees C). The chitosan (2.93 %) and postbiotic (20.08 %) concentrations in the films were determined by using the Box-Behnken method. The characterization analyses shows that postbiotic contains various bioactive ingredients, e.g. free amino acids and volatiles. The prepared films exhibited high mechanical strength, antibacterial properties, and low water vapor permeability. In the rainbow trout fillet experiment, untreated samples (C4 and C10) exceeded the permissible total viable count (7.0 log(10)) limit on day 6 and 15. However, the edible film-treated fillets stored at 10 degrees C (F10) reached the limit on the 21st day, and the film-treated fillets stored at 4 degrees C (F4) did not reach the limit over a 24 days period (P < 0.05). The film application resulted in an extension of the shelf-life by 18 days without any major modification of color and organoleptic characteristics of the fillets (P > 0.05). The results indicate that the postbiotic of P. acidilactici contained abundant bioactive products and that the edible film prepared by the addition of postbiotic and chitosan could extend the shelf life of trout fillets through antimicrobial effects and antioxidant stabilization.
Keywords: Rainbow trout; Postbiotic; Chitosan; Edible film; Shelf life; Mechanical strength; Vapor permeability